Extragnathic and gnathic odontome - Muthu Sekhar; Loganathan Selvaraj (Wolters Kluwer Medknow Publications, 2015)
This is a very rare case report of a multiple odontome involving the upper jaws, lower jaws and an extragnathic site. A thirty seven year-old male complained of missing teeth in his left upper and lower jaw since childhood. Radiographic examination revealed multiple calcified teeth like structures in the left side of the patient's maxilla, mandible and mastoid region of skull base. We arrived at the diagnosis of compound odontome. Patient was otherwise systemically normal and with good health. He underwent surgical enucleation of the jaw odontome while the extragnathic odontome was left under observation. This rare case report proves that the embryonic dental cells might migrate to the primordium of the Rathke's pouch and further might be carried towards the site of the developing cranial base region.